Paging strategy optimization in personal communication systems - Abutaleb, Ahmed; Li, Victor O.K. (Wireless networks, 1997)
Mobility tracking is concerned with finding a mobile subscriber (MS) within the area serviced by the wireless network. The two basic operations for tracking an MS, location updating and paging, constitute additional load on the wireless network. The total cost of updating and paging can be minimized by optimally dividing the cellular area into location registration (LR) areas. In current systems broadcast paging messages are sent within the LR area to alert the MS of an incoming call. In this paper we propose a selective paging strategy which uses the MS mobility and call patterns to minimize the cost of locating an MS within an LR area subject to a constraint on the delay in locating the MS.